Evolution of Cold Acclimation and Its Role in Niche Transition in the Temperate Grass Subfamily Pooideae. Issue 1 (8th March 2019) - Schubert, Marian; Grønvold, Lars; Sandve, Simen R.; Hvidsten, Torgeir R.; Fjellheim, Siri
Abstract : Comparative analysis of cold response in Pooideae species shows that cold acclimation is common in Pooideae but that this adaptation has largely evolved independently in different tribes. Abstract: The grass subfamily Pooideae dominates the grass floras in cold temperate regions and has evolved complex physiological adaptations to cope with extreme environmental conditions like frost, winter, and seasonality. One such adaptation is cold acclimation, wherein plants increase their frost tolerance in response to gradually falling temperatures and shorter days in the autumn. However, understanding how complex traits like cold acclimation evolve remains a major challenge in evolutionary biology. Here, we investigated the evolution of cold acclimation in Pooideae and found that a phylogenetically diverse set of Pooideae species displayed cold acclimation capacity. However, comparing differential gene expression after cold treatment in transcriptomes of five phylogenetically diverse species revealed widespread species-specific responses of genes with conserved sequences. Furthermore, we studied the correlation between gene family size and number of cold-responsive genes as well as between selection pressure on coding sequences of genes and their cold responsiveness. We saw evidence of protein-coding and regulatory sequence evolution as well as the origin of novel genes and functions contributing toward evolution of a cold response in Pooideae. Our results reflect that selection pressure resulting from global cooling must have acted on already diverged lineages. Nevertheless, conservation of cold-induced gene expression of certain genes indicates that the Pooideae ancestor may have possessed some molecular machinery to mitigate cold stress. Evolution of adaptations to seasonally cold climates is regarded as particularly difficult. How Pooideae evolved to transition from tropical to temperate biomes sheds light on how complex traits evolve in the light of climate changes.